Fikih Kontemporer Dalam Dakwah Gus Baha di Media Sosial - Jamal, Syukron (Rumah Jurnal Institut Agama Islam An-Nawawi Purworejo, 2024)
This study aims to analyze how Gus Baha's popularity on the YouTube social media platform, the contemporary fiqh istinbat (legal derivation) methods he applies, and his digital preaching characteristics influence public acceptance of Islamic preaching in the digital era. The research employs a qualitative approach using discourse analysis to explore primary data from Gus Baha’s sermons uploaded on YouTube and secondary data from related academic literature. The analysis is conducted to understand the application of contemporary fiqh istinbat methods in Gus Baha’s sermons and their impact on audience reception. The findings indicate that Gus Baha's popularity on YouTube is highly significant, with the keyword